Design of a gamification strategy to intervene in social and human factors associated with software process improvement change resistance - Gloria Piedad Gasca‐Hurtado; María Clara Gómez‐Álvarez; Liliana Machuca‐Villegas; Mirna Muñoz (IET Software)
Abstract Best practices of software development and software process improvement (SPI) are people‐centred. Both have a high level of influence of social and human factors inherent to the individuals involved in these processes. At the same time, software process improvement is inherent to the change of the conditions and the behaviour of individuals. In this work, the authors show the results of applying a deductive approach for a method based on gamification and social and human factors to influence the productivity of the software development team. The results show that it is possible to abstract all the design aspects of an existing strategy called Interplanetary Mission and identify the social and human factors involved in change resistance in SPI initiatives. The strategy execution results show that gamification strategies could help to mitigate change resistance in SPI initiatives for software development teams and their productivity, understanding this term in software engineering context as the ratio between output and input within the software development production process.